The Impact of the COVID-19 Pandemic on the Compliance Level of Annual SPT Reporting for Individual Taxpayers at the Pondok Aren Tax Service Office, South Tangerang City - Ambarwati Ambarwati; Indra Sumarna Sobari; Rudi Kristanto (Yayasan Ilomata, 2021)
Indonesia has recorded a total of 1,626,812 positive cases of covid 19, 44,172 people died, recovered 1,481,449 people (last update: April 22, 2021; data source www.Covid19.go.id). The outbreak of the coronavirus or Covid-19 that hit the whole world, Indonesia was also affected by changes in the economy becoming unstable, causing the wheels of business to be hampered or even some have stopped their activities for the next few days. The impact experienced by all taxpayers throughout the country is affected, at least it is enough to make activities in this country not conducive. The decline in the level of the Indonesian economy experienced a very significant decline. The government's policy in fighting this epidemic must be supported from all aspects and levels of society, in line with the government's policy of the Directorate General of Taxes (DGT) of the Ministry of Finance providing relaxation in the form of simplifying the submission of documents for completing annual notification letters or SPT, in conditions of the Covid-19 pandemic This relaxation is provided for corporate taxpayers and individual taxpayers. The low tax revenue due to the impact of the Covid-19 pandemic is a consequence that the government must accept. This study is to find out whether there is an influence on understanding tax regulations, the method used in this study uses a quantitative method based on tax rates and the principle of justice on mandatory compliance, the impact of the Covid 19 Pandemic disaster on the level of compliance with the annual SPT reporting of individual and corporate taxpayers. The Utilization of Information Technology significantly affects taxpayer compliance.